2003
DOI: 10.1088/0953-8984/15/40/009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of host glass on optical absorption and fluorescence of Nd3+inxNa2O–(30 x)K2O–70B2O3glasses

Abstract: The effect of host glass composition on the optical absorption and fluorescence spectra of Nd 3+ has been studied in mixed alkali borate glasses of the type 5, 10, 15, 20 and 25). Various spectroscopic parameters such as Racah (E 1 , E 2 and E 3 ), spin-orbit (ξ 4f ) and configuration interaction (α, β) parameters have been calculated. The Judd-Ofelt intensity parameters ( λ ) have been calculated and the radiative transition probabilities (A rad ), radiative lifetimes (τ r ), branching ratios (β) and integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…The details of preparation of these glasses were given in the authors earlier article [17]. The samples examined in the present work are…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of preparation of these glasses were given in the authors earlier article [17]. The samples examined in the present work are…”
Section: Methodsmentioning
confidence: 99%
“…Table 5 gives peak wavelengths (l P ), radiative transition probabilities (A rad ), effective linewidths (Dl eff ) and stimulated emission cross-sections (s p ) of 4 F 3/2 -4 I 13/2 , 4 F 3/2 -4 I 11/2 and 4 F 3/2 -4 I 9/2 CW laser action. These values for 4 F 3/2 -4 I 11/2 transition are high for lithium sodium and lithium potassium glasses when compared with sodium potassium glass [17]. It is also observed that s p value increases when the third component is added to the glass matrix [26].…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulated emission cross-section between 4 F 3/2 -4 I J 0 having measured fluorescence lifetime (t f ) is given as below [24] s em ¼ l 4 p 8pcn l p À Á 2 Dl eff A½ðaJÞ; ðaJ 0 Þ,…”
Section: Fluorescence Spectra and Decay Analysismentioning
confidence: 99%
“…Large stimulated emission cross sections have been reported [9] stressing the suitability of different Nd 3+ doped lead borate and bismuth borate glasses for laser action. Studies of NMR and fluorescence of Nd 3+ doped binary alkali borate glasses have also been published [10,11]. However, to the best of our knowledge, rare earth doped alkali lead borate glasses have not been studied in any great detail.…”
Section: Introductionmentioning
confidence: 99%